Messages Contained In The Short Film "Tilik" - Amalia; Syahminan, Mhd.; Rasyid, Abdul (International Journal of Cultural and Social Science, 2022)
The purpose of this qualitative research is to find out: 1) how the moral messages contained in the short film Tilik, 2) whether the moral messages contained in the short film Tilik can build a bad image of Islam. Data collection techniques using observation and documentation. Sources of data from this study are divided into sources, namely primary data sources (Tilik film) and secondary data sources (internet, books, and related journals). The data were analyzed using Roland Barth's semiotic approach. Semiotics Roland Barthes uses the concept of denotation, connotation and myth as the meaning of the message. The research findings show that: 1) the moral messages in the short film Tilik are, the moral messages are visiting the sick, backbiting or gossiping, prejudice, criticizing, bribing, prohibiting slander, selfishness, helping, violating regulations, and spreading hoax news. 2) based on the moral message in this study, it was found that the Tilik film builds a bad image of Islam.